Research of professional value orientations formation of future doctors - Murzina, O. A.; Makyeyeva, L. V.; Raznatovska, O. M.; Pototska, O. I.; Hvinivetska, N. V.; Vovchenko, M. B.; Shcerbacov, M. S.; Мурзіна, Олена Анатоліївна; Макєєва, Людмила Валеріївна; Разнатовська, Олена Миколаївна; Потоцька, Олена Іванівна; Грінівецька, Наталія Валеріївна; et al. (My University, 2022)
Medical education is based on general and specialized knowledge in the learning process, a combination of theory and practice at a medical university and is the foundation of the medical profession. But the formation of professional value orientations of future doctors remains out of consideration. Therefore, the professional training of future doctors needs the content of medical education to be improved in order to focus on the formation of professional values.